PRODUÇÃO E ANÁLISE DOS EFEITOS IMUNOBIOLÓGICOS DE NANOCÁPSULAS POLIMÉRICAS DE NÚCLEO AQUOSO SOBRE CÉLULAS DENDRÍTICAS MURINAS - Possani, Liliane Medianeira Mayer (2015)
Herpes is a condition caused by Herpes Simplex Virus types 1 (HSV-1) and 2 (HSV-2) which largely affects the global population. Both species can be transmitted through direct contact with infected lesions or biological fluids such as saliva and genital fluids. However, asymptomatic carriers can also transmit and excrete virus. Control of herpes is accomplished through the use of antiviral drugs, however, its extensive use has led to the emergence of resistant virus strains, particularly in immunocompromised patients. Because of that the development of an effective vaccine will not only control the disease, but also its etiologic agent. HSV-1 is an enveloped DNA viruses, and in this envelope there are viral glycoproteins that are responsible for the process of entering into the host cell. The mainly glycoproteins are B (gB) glycoprotein D (gD), glycoprotein H (gH) and glycoprotein L (gL). Glycoprotein B is the most studied protein and the reason for that is because its sequence is conserved among all herpesviruses and also is essential for the cell infection process. In this glycoprotein there is a fragment of 8 amino acid residues referred SSIEFARL. It is an immunodominant peptide responsible for inducing a strong T cell response upon infection process. This peptide is poorly immunogenic when adminstered without protection and or adjuvant. Thus, the nanobiotechnology can help for the development of a potent adjuvant to protect SSIEFARL and increase its immunogenicity. For this propouse, the production of previous developed polymeric nanocapsules (NCPs) with aqueous core was otimized and its physical and chemical parameters determined. After otimization, the encapsulation efficiency of SSIEFARL was evaluated and the interaction/compatibility of unloaded NCPs with cell in vitro were also determined. The NCPs presented unimodal distribution, low PDI (0.23±0.03), mean diameter of 267.5±51.6 and zeta potential -29.6±2.2, pH 7.2±0.3. The analyzes showed that 98% (97.7±1.5) of the particles in the sample were in the nanoscale and the a concentration of NCPs 6,07x1010/cm3. In vitro tests showed no cytotoxicity, and unload NCPs and in vivo tested suggest a cell migration to the site of injection and draning to the reagional lymph nodes, suggesting some adjuvant propertie. Taken together, the data suggest that the NCPs can be used in the development of an adjuvant system for the protection of SSIEFARL and development of a vaccine against HSV-1.